2016
DOI: 10.1155/2016/7951272
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Nasal Delivery of Humidified and Warmed Air at Different Temperatures: A Randomised Double-Blind Pilot Study

Abstract: Objectives. Delivery of warmed, humidified air via nasal high flow therapy could potentially reduce replication of temperature-sensitive viruses in the upper respiratory tract. This study investigates whether nasal high flow therapy is well tolerated by healthy adults at 37°C and 41°C. Methods. In this randomised, double-blind, controlled crossover pilot trial, nasal high flow therapy was used to deliver humidified air at 35 L/min, at either 37°C or 41°C, for three one-hour sessions of use over one day. The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The WHO laboratory work shows that heat at 56ºC kills the SARS coronavirus at around 10,000 units per 15 min. This could pave way for a potential therapeutic prospect of warm steam inhalation/heated humidified air delivery/rhinothermy, which has been traditionally and clinically proven to be potent against viral upper respiratory tract infections [17][18][19].…”
Section: Therapeutic Prospectsmentioning
confidence: 99%
“…The WHO laboratory work shows that heat at 56ºC kills the SARS coronavirus at around 10,000 units per 15 min. This could pave way for a potential therapeutic prospect of warm steam inhalation/heated humidified air delivery/rhinothermy, which has been traditionally and clinically proven to be potent against viral upper respiratory tract infections [17][18][19].…”
Section: Therapeutic Prospectsmentioning
confidence: 99%
“…These are similar to observations made in our earlier tolerability of the myAIRVO device in healthy volunteers. 26 In the current study, participants used the myAIRVO 2 device for 2 hours per day on average throughout the 5-day treatment period and for 2.6 hours on the days of use. As instructed, not all participants used the device late in the treatment course once their symptoms had improved.…”
Section: Discussionmentioning
confidence: 99%
“…21 We have reported a tolerability study that found that a high flow nasal cannula device (myAIRVO 2, Fisher & Paykel Healthcare, Auckland, New Zealand) modified to deliver high flow humidified air at 41°C via wide bore nasal cannulae was well tolerated in healthy volunteers. 26 The potential advantage of this device for rhinothermy is that it can deliver a consistent temperature, humidity and flow rate direct into the upper airways. The study reported here is a feasibility study of rhinothermy in the treatment of the common cold that will inform the design of a robust RCT of this treatment.…”
Section: Open Accessmentioning
confidence: 99%
“…36 Public health students' knowledge will be enhanced if researches are done in Covid-19 quarantine centers to authenticate the suspected prevention regimens of internalized and externalized hot water, frequent gargling, hourly ingestion of hot beverages and especially continuous nasal steam delivery for 30 -60 minutes during the very early stage of the virus infection. 37,16 Limitations of the study This study is based on a small convenient sample, without randomization, and thus results cannot be generalized. The survey instrument was not verified through key witness interviews or focus group to determine clarity of understanding by study participants.…”
Section: Recommendationmentioning
confidence: 99%
“…15 Since respiratory viral pathogens are temperature sensitive, continuous nasal steam delivery for thirty to sixty minutes has the potential to cure URTI or common cold, humanity's most frequent infection unlike steam inhalation which merely relieves the symptom. 16,17 Though the mechanism of action is yet unknown, gargling with fluids e.g tap water, saline water etc is one of the measures long recommended by Japanese health authority to prevent upper respiratory tract infections caused by rhinovirus, coronavirus, influenza virus, pneumococci, streptococci etc. 18 Experience in clinical dentistry reveals the prevailing ignorance surrounding health effects of cold beverages.…”
Section: Introductionmentioning
confidence: 99%